2013
DOI: 10.1136/bcr-2012-007482
|View full text |Cite
|
Sign up to set email alerts
|

Oral cysticercosis: a clinical dilemma

Abstract: Cysticercosis is a potentially fatal parasitic disease caused by cysticercus cellulosae, the larval stage ofTaenia solium. Oral cysticercosis is a rare entity and represents difficulty in clinical diagnosis. This article reports two cases of oral cysticercosis involving buccal and labial mucosa. Both the cases presented with solitary, nodular swelling that had been clinically diagnosed as a mucocele. Histopathology of excisional biopsy revealed it to be cysticercosis. Single, cystic nodular swelling of oral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Wanjari et al reported two cases of oral cysticercosis involving buccal and labial mucosa. Both the cases presented with solitary, nodular swelling that had been clinically diagnosed as a mucocele …”
Section: Discussionmentioning
confidence: 99%
“…Wanjari et al reported two cases of oral cysticercosis involving buccal and labial mucosa. Both the cases presented with solitary, nodular swelling that had been clinically diagnosed as a mucocele …”
Section: Discussionmentioning
confidence: 99%
“…T. solium has a two-host cycle with pig and human beings as the intermediate host, providing the niche to the larvae of cystercerci to survive while human beings are the sole definitive host which foster the adult tapeworm. [ 2 ] The parasite infection spreads through the oro-faecal route by ingesting the food infested with the eggs of the organism. Consumption of infected under-cooked pork is the major cause of CC, while the reasons for its occurrence in the vegetarians can be attributed to eating raw vegetables irrigated with infected water source or drinking infected water.…”
Section: Life Cycle and Human Infestationmentioning
confidence: 99%
“…[ 3 ] The treatment includes surgical enucleation for solitary lesions and potent anti-helminthics like praziquantel and albendazole can be used for symptomatic or disseminated cases or where surgical intervention is risky or not possible, e.g., Neurocysticercosis. [ 2 ]…”
Section: Oral Manifestationmentioning
confidence: 99%
See 1 more Smart Citation